The Role of Family Functioning in Emotional Regulation among Adolescents from Broken Homes - Lathessya Wirio; Jeslina; Jesslyn; Rina Mirza; Winida Marpaung (Fakultas Psikologi Universitas Yudharta Pasuruan, 2026)
Changes in family structure due to divorce and conflict have increased the number of adolescents living in broken homes. This condition not only has an impact on the social aspect, but also on the emotional development of adolescents. This study aims to examine the relationship between family functioning and emotional regulation of broken home adolescents. The study used a correlational quantitative approach involving 135 broken home adolescents as research subjects. Data collection was carried out using the family functioning scale and the emotion regulation scale. The results of data analysis with the Pearson product moment correlation technique show that there is a significant positive relationship between family functioning and emotion regulation ability, where the better the functioning of the family, the better the ability of adolescents to manage emotions. In contrast, families that do not function optimally tend to be associated with a teen's low ability to manage emotions. These findings confirm the importance of the role of the family in supporting adolescent emotional development and can be the basis for the development of psychological interventions and educational programs that focus on strengthening family function and emotion regulation skills.